2023
DOI: 10.1149/1945-7111/ad09f9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Measurement of Water Transport Numbers in Anion-Exchange Membranes

John G. Petrovick,
Douglas I. Kushner,
Priyamvada Goyal
et al.

Abstract: Anion-exchange membranes (AEMs) are a possible replacement for perfluorosulfonic-acid membranes in energy-conversion devices, primarily due to the hydroxide mobile ion allowing the devices to operate in alkaline conditions with less expensive electrocatalysts. However, the transport properties of AEMs remain understudied, especially electro-osmosis. In this work, an electrochemical technique, where the open-circuit voltage is measured between two ends of a membrane maintained at different relative humidities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…As indicated in previous studies, , one possible failure mode of the forward-bias BPM CO 2 electrolyzer is the delamination issue between the AEL and PEL, which is projected to result in increase of contact resistance. However, this behavior is not observed for the asymmetrical BPMs in this study, as shown by the descending trend and plateauing behavior of the HFR, which further illustrates the superiority of asymmetrical design of BPM with thinner AEL to allow for efficient CO 2 back diffusion from the bipolar junction to the cathode and possible improved heat and water management at the bipolar junction. , …”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…As indicated in previous studies, , one possible failure mode of the forward-bias BPM CO 2 electrolyzer is the delamination issue between the AEL and PEL, which is projected to result in increase of contact resistance. However, this behavior is not observed for the asymmetrical BPMs in this study, as shown by the descending trend and plateauing behavior of the HFR, which further illustrates the superiority of asymmetrical design of BPM with thinner AEL to allow for efficient CO 2 back diffusion from the bipolar junction to the cathode and possible improved heat and water management at the bipolar junction. , …”
Section: Resultsmentioning
confidence: 55%
“…However, this behavior is not observed for the asymmetrical BPMs in this study, as shown by the descending trend and plateauing behavior of the HFR, which further illustrates the superiority of asymmetrical design of BPM with thinner AEL to allow for efficient CO 2 back diffusion from the bipolar junction to the cathode and possible improved heat and water management at the bipolar junction. 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…−1 ) a significantly larger value of 2.5 was obtained. Recently, Petrovick et al 17 investigated the water transport in a similar ex situ setup for Nafion and several anion exchange membranes. It was found that the proton drag coefficient increases from < 2 for 20 °C to ∼3 at 50 °C in a humidification range of 4-10 mol H2O mol SO3 −1 .…”
Section: List Of Symbolsmentioning
confidence: 99%